Pengaruh Waktu Dan Temperatur Hidrolisis Dalam Proses Sintesis Furfural Dari Sekam Padi Dengan Menggunakan Metode Hidrolisis Dan Dehidrasi - Amborowati, Cindi; Adriani, Uni; Aditya, Indah Lukyta; Feviasari, Hanifati; Hastin, Tidar Kumala; Adhiksana, Arief (Journal of Research and Technology, 2016)
Rice fields in East Kalimantan is one of productive land. It looks from many piles of rice husk waste in rice milling. The rice husk waste has not been used much, so this research used the rice husk waste as raw material of furfural manufacturing. This research has three stages, there are raw material preparation, hydrolysis, and product analysis. At the preparation stage, rice husk is diminished to 100 mesh, then dried in oven. Hydrolysis process used sulfuric acid 1% as catalyst with the variation times were 10, 40, 70, 100, 130 (minutes) and temperature are 30, 50, 70, 90, 105 (°C). Then hydrolysis result was filtered and the filtrate was quantitatively analyzed by volumetric method. Highest result of time variation obtained was at 130 minutes with furfural concentration as much 8,182 mol/L, while highest result of temperature variation obtained was at 105 °C with furfural concentration as much 10,741 mol/L.